Recent Development of Drug Delivery Systems through Microfluidics: From Synthesis to Evaluation - Zhiyuan Ma; Baicheng Li; Jie Peng; Dan Gao (MDPI AG, 2022)
Conventional drug administration usually faces the problems of degradation and rapid excretion when crossing many biological barriers, leading to only a small amount of drugs arriving at pathological sites. Therapeutic drugs delivered by drug delivery systems to the target sites in a controlled manner greatly enhance drug efficacy, bioavailability, and pharmacokinetics with minimal side effects. Due to the distinct advantages of microfluidic techniques, microfluidic setups provide a powerful tool for controlled synthesis of drug delivery systems, precisely controlled drug release, and real-time observation of drug delivery to the desired location at the desired rate. In this review, we present an overview of recent advances in the preparation of nano drug delivery systems and carrier-free drug delivery microfluidic systems, as well as the construction of in vitro models on-a-chip for drug efficiency evaluation of drug delivery systems. We firstly introduce the synthesis of nano drug delivery systems, including liposomes, polymers, and inorganic compounds, followed by detailed descriptions of the carrier-free drug delivery system, including micro-reservoir and microneedle drug delivery systems. Finally, we discuss in vitro models developed on microfluidic devices for the evaluation of drug delivery systems, such as the blood-brain barrier model, vascular model, small intestine model, and so on. The opportunities and challenges of the applications of microfluidic platforms in drug delivery systems, as well as their clinical applications, are also discussed.